A Study Of Digital Video Expression Using Double Projection Mapping Techniques - Suhaimi, Lim (Universiti Malaysia Sarawak (UNIMAS), 2018)
This research is about creating a digital video expression by using double projection mapping in order to create a new genre of projection mapping. The purpose of the research is to investigate the characteristics of using two projector in projection mapping through experimentation.